MEKTEP OQÍWShÍLARÍNDA ERKIN PIKIRLEW HÁM ILIMIY IZLENIWShEŃLIKTI QÁLIPLESTIRIW USÍLLARÍ - Kosnazarov, S.T. (SCIENCE and SOCIETY, 2025)
An important goal of modern education is the development of students’ creative thinking. This is quite understandable, as our current successes or failures are largely determined by our ability (or inability) to demonstrate flexibility and analytical thinking in complex life situations. Based on this, the issues of fostering free thinking in schoolchildren in the modern education system and forming scientific creativity on this basis, as well as their solutions, have found their scientific confirmation in our article.